Budidaya Maggot BSF: Solusi Sampah Organik dan Pakan Ternak Lele di Desa Nagrak: Pengabdian - Fadhillah Azzahra; Musyafa Abdillah; R.M. Abdurrohim; Amelia Putri; Shani Azhara; Shaumy Adellya N; Aldi Zaidahanis; Salman Herlambang; Fajar Yunawwirudin Haq; Siti Rahmawati; Muhamad Iqbal Rhamadianto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Community Service Program (KKN) conducted by Muhammadiyah University of Bandung in Nagrak Village aims to empower the community in maintaining environmental cleanliness in accordance with the potential of the region and available human resources. Specifically, this activity is aimed at enabling students to identify problems, foster community awareness of the environment, and encourage the community to cultivate Black Soldier Fly (BSF) Maggots as an alternative for managing organic waste. The research used a qualitative approach through field surveys, interviews, and secondary data analysis. The survey was conducted to determine the condition of waste management, while interviews with village officials, community leaders, and youth aimed to explore needs and appropriate solutions. The Maggot management program was implemented with an educational approach through socialization, namely providing an understanding of the differences between organic and non-organic waste and the benefits of Maggots in decomposing organic waste quickly and efficiently. The results of the activity showed an increase in community understanding and awareness in sorting waste, as well as the use of Maggots as alternative feed, for example for catfish. Thus, Maggot management not only contributes to reducing the volume of organic waste but also opens up new, environmentally friendly economic opportunities.